PENDAMPINGAN SUAMI DALAM KEIKUTSERTAAN PROGRAM KELUARGA BERENCANA MELALUI PERBAIKAN PEMAHAMAN TENTANG METODE KONTRASEPSI KELURAHAN BINTARORE KECAMATAN UJUNG BULU KABUPATEN BULUKUMBA - Jusni Jusni; Erniawati Erniawati; Nurul Hidayah Bohari; Darliana Darwis (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2021)
Male participation is one of the problems that are still faced in family planning programs in several countries, including Indonesia. Family planning programs that focus on women in a society that adheres to a patriarchal system give the impression that women are the ones who are responsible for managing pregnancy. This community service program aims to encourage husbands' participation in family planning programs through improving their understanding of contraceptive methods. After participating in this activity, it is hoped that husbands will have broad knowledge about contraceptive methods. This community service is carried out in an integrated manner through the PKK activity for the Tahirah Al Baeti Bulukumba Midwifery Community in 2021 in the Menara Environment, Bintarore Village, Kec. Ujung Bulu, Bulukumba Regency. The approach taken is through mentoring as a form of community engagement and education about myths and facts about contraceptive methods and family planning. This community service program has been proven to be able to significantly increase men's knowledge on family planning issues. Community involvement, starting from the process of determining problem priorities, makes the interventions that are carried out truly become community needs. This indirectly causes the target to participate actively during the activity, so that his knowledge of family planning increases.